Sudden Death and Coronary Artery Anomalies - Rizzo, Stefania; De Gaspari, Monica; Frescura, Carla; Padalino, Massimo; Thiene, Gaetano; Basso, Cristina (Frontiers in Cardiovascular Medicine, 2021)
Congenital coronary artery anomalies (CAA) include a wide spectrum of malformations present at birth with various clinical manifestations and degrees of severity. Patients may be asymptomatic, and CAA may be an incidental finding during cardiac imaging or at autopsy. However, in other cases, ischemia-related signs and symptoms, leading to an increased risk of sudden cardiac death (SCD), often as first presentation may occur. In this chapter, we discuss the normal anatomy of the coronary arteries (CA) and the pathology of CAA at risk of SCD, including our experience with victims of SCD among the young population (age <40 years) and among athletes.